The city : suggestions for investigation of human behavior in te urban environment - Park, Robert E. (The University of Chicago Press, 1967)
The City, first published in 1925 and reprinted here in its entirety, is a cross-section of concerns of the Chicago urban school during the period of its most intense activity. Park and Burgess realized that ecological and economic factors were converted into a social organization by the traditions and aspirations of city dwellers. In their efforts to achieve objectivity, these sociologists never lost sight of the values that propel human beings.